Cellulitis Caused by Hirudo orientalis Bites That Lead to an Allergic reaction - Mohsen Najjari; Rahmat Solgi; Amir Tavakoli Kareshk (Case Reports in Infectious Diseases)
The allergic reaction due to leech bites is frequently reported due to complications of leech therapy and also unwanted leech infestation. Regularly, the urticarial papules are common, and itching lasts less than 24 h. In the case of leech biting, dermal infection could be caused by leech gut bacterial flora such as Aeromonas spp and histamine from leech saliva. In this case report, a 30-year-old diabetic woman, who works in the field of leech breeding, was bitten by Hirudo orientalis during breeding. Her clinical signs were inflammation, swelling, pain, and redness in the back of her left hand. A microbiological examination revealed that the isolated leech was infected with Aeromona hydrophila. The risk of death due to anaphylactic shock and sepsis is high in some cases of underlying diabetes and immunocompromised individuals. The study pointed out the hazards of leech bites and proposed preventative measures such as using gloves and boots for farm workers.